Graphene-magnetite as adsorbent for magnetic solid phase extraction of 4-hydroxybenzoic acid and 3,4-dihydroxybenzoic acid in stingless bee honey - Musa, Marina; Wan Ibrahim, Wan Aini; Mohd Marsin, Faridah; Abdul Keyon, Aemi S.; Rashidi Nodeh, Hamid (Food chemistry, 2018)
•Synthesis of new graphene-magnetite solid phase extraction sorbent (G-Fe3O4-MSPE).•Fast and green extraction method for two phenolic acids in stingless bee honey.•Efficient extraction of phenolic acids with low detection limits (0.08–0.14 µg/g).•A method with good relative recoveries (72.6–110.6%) and precision values. Graphene-magnetite composite (G-Fe3O4) was successfully synthesized and applied as adsorbent for magnetic solid phase extraction (MSPE) of two phenolic acids namely 4-hydroxybenzoic acid (4-HB) and 3,4-dihydroxybenzoic acid (3,4-DHB) from stingless bee honey prior to analysis using high performance liquid chromatography with ultraviolet–visible detection (HPLC-UV/Vis). Several MSPE parameters affecting extraction of these two acids were optimized. Optimum MSPE conditions were 50 mg of G-Fe3O4 adsorbent, 5 min extraction time at 1600 rpm, 30 mL sample volume, sample solution pH 0.5, 200 µL methanol as desorption solvent (5 min sonication assisted) and 5% w/v NaCl. The LODs (3 S/N) calculated for 4-HB and 3,4-DHB were 0.08 and 0.14 µg/g, respectively. Good relative recoveries (72.6–110.6%) and reproducibility values (RSD < 8.5%, n = 9) were obtained. The developed G-Fe3O4 MSPE method offered is simple, easy, environmental friendly and efficient for extraction of the two phenolic acids from stingless bee honey samples.